2019
DOI: 10.2172/1615815
|View full text |Cite
|
Sign up to set email alerts
|

Sister Rod Destructive Test Results (FY19)

Abstract: This report documents work performed under the Spent Fuel and Waste Disposition, Spent Fuel and Waste Science and Technology program for the US Department of Energy (DOE) Office of Nuclear Energy (NE). This work was performed to fulfill Level 2 Milestone M2SF-19ORO010201026 within work package SF-19OR01020102 and is an update to the work reported in M2SF-19OR010201028 and M3SF-19OR010201027. The document incorporates comments received with respect to the previous reports and incorporates additional test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Two UO 2 fuel rods from an Advanced Mark-BW fuel assembly that had been irradiated in a Westinghouse PWR at the North Anna Power Station were selected based on similar burnup and fuel-cladding compositions for the leaching experiments [12]. Of the two samples, one has been heat treated to fuel drying temperatures as described in the sister rod destructive examinations (DE) report [11]. The rod specimens chosen were residues from the CIRFT experiment addressed in the sister rod reports.…”
Section: J-21 Fuel Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Two UO 2 fuel rods from an Advanced Mark-BW fuel assembly that had been irradiated in a Westinghouse PWR at the North Anna Power Station were selected based on similar burnup and fuel-cladding compositions for the leaching experiments [12]. Of the two samples, one has been heat treated to fuel drying temperatures as described in the sister rod destructive examinations (DE) report [11]. The rod specimens chosen were residues from the CIRFT experiment addressed in the sister rod reports.…”
Section: J-21 Fuel Specimensmentioning
confidence: 99%
“…Average measurements of the cladding thickness, pellet thickness, PCI layer, porosity, and HBU rim regions were provided for both samples, as shown in [11] and the gamma scanning, eddy current, and LVDT measurements provided in the nondestructive examination (NDE) report [13]. The PCI layer is visible throughout the perimeter of the fuel pellet, extending in the range of 9-15 µm.…”
Section: J-334 Combined Release Ratesmentioning
confidence: 99%
“…One rod was heat treated to an average temperature of 409.4°C (Table J-1). The heat treatment was part of a separate study to analyze hydride re-orientation in the cladding [11]. Although the presence of hydrides in the cladding is not expected to have an effect on the leaching phenomenon, it has been observed that hydride realignment can reduce cladding strength, allowing water to more easily penetrate into the gaps and grain boundaries in the fuel's periphery.…”
Section: J-2 Experimentsmentioning
confidence: 99%
“…Two UO2 fuel rods from an Advanced Mark-BW fuel assembly that had been irradiated in a Westinghouse PWR at the North Anna Power Station were selected based on similar burnup and fuel-cladding compositions for the leaching experiments [12]. Of the two samples, one has been heat treated to fuel drying temperatures as described in the sister rod destructive examinations (DE) report [11]. The rod specimens chosen were residues from the CIRFT experiment addressed in the sister rod reports.…”
Section: J-21 Fuel Specimensmentioning
confidence: 99%
See 1 more Smart Citation